(untitled) (Applied Biological Research, 2018)
The in vivo methods for rearing of entomopathogenic nematodes requires large quantities of insect hosts like greater wax moth, Galleria mellonella (L.) which involves more time and additional costs, necessitates alternative host for multiplication of entomopathogenic nematodes. The present study was aimed to assess the infectivity and multiplication of two entomopathogenic nematodes, Heterorhabditis bacteriophora Poinar and Steinernema sp. isolated from Majuli river island of Assam in subterranean termiteOdontotermes obesus (Ramb). The laboratory tests using Petri-dishes, illustrated the effectiveness of both the nematodes against O. obesus at 100 IJs termite-1(worker/soldier) within 24-48 h, in which the nematodes could reproduce in 5-7 days. The natural mounds (250 g) containing O. obesus (80-100 workers/ soldiers/nymphs) were also inoculated with H. bacteriophora and Steinernema sp. at 1000 IJs and incubated at room temperature (30±2oC) up to 20 days for multiplication. Following the Cobb decanting and sieving method, the results exhibited the optimum yields of 30,000 and 25,000 IJs of H. bacteriophora and Steinernema sp., respectively, at 15 days beyond which the IJs starts deterioration. Under laboratory condition entomopathogenic nematodes H. bacteriophora and Steinernema sp. can be reared and mass produced for further management practices against termite.